1988
DOI: 10.1021/bi00406a065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the ligands of beef tryptophanyl-tRNA synthetase on the elementary steps of the tRNATrp aminoacylation

Abstract: Tryptophanyl-tRNA synthetase catalyzed formation of Trp-tRNA(Trp) has been studied by mixing tRNA(Trp) with a preformed bis(tryptophanyl adenylate)-enzyme complex in the 0-60-ms time range, on a quenched-flow apparatus. Analyzing the data gives an association rate constant ka = (1.22 +/- 0.47) X 10(8) M-1 S-1, a dissociation rate constant kd = 143 +/- 73 S-1, and a dissociation constant Kd = 1.34 +/- 0.80 microM for tRNA(Trp). The maximum rate constant of tryptophan transfer to tRNA(Trp) is kt = 33 +/- 3 S-1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Taking into account rather low affinity of tRNA for the E site of 80S ribosomes (the apparent K d is about 600 n m [33]), it is plausible to assume that the transfer of tRNA from the E site to eEF1A·GDP occurs due to the affinity gradient ( K d for [eEF1A·GDP·tRNA] is 20 n m , this study). Furthermore, the ARS affinity for [eEF1A·GDP·tRNA] ( K d is 9 n m , this study) is higher than that for free tRNA ( K d in the range of 100–200 n m [34,35]), which makes association of the enzyme with tRNA bound to eEF1A·GDP thermodynamically favorable. In this quaternary complex, a transfer of tRNA from the factor to ARS may occur.…”
Section: Vectorial Transfer Of Trna/aminoacyl‐trna During Mammalian Tmentioning
confidence: 80%
“…Taking into account rather low affinity of tRNA for the E site of 80S ribosomes (the apparent K d is about 600 n m [33]), it is plausible to assume that the transfer of tRNA from the E site to eEF1A·GDP occurs due to the affinity gradient ( K d for [eEF1A·GDP·tRNA] is 20 n m , this study). Furthermore, the ARS affinity for [eEF1A·GDP·tRNA] ( K d is 9 n m , this study) is higher than that for free tRNA ( K d in the range of 100–200 n m [34,35]), which makes association of the enzyme with tRNA bound to eEF1A·GDP thermodynamically favorable. In this quaternary complex, a transfer of tRNA from the factor to ARS may occur.…”
Section: Vectorial Transfer Of Trna/aminoacyl‐trna During Mammalian Tmentioning
confidence: 80%
“…Tryptophan was shown to bind competitively with charged tRNA Trp (Trp‐tRNA Trp ) to bovine TrpRS (Trezeguet et al , 1986). As a consequence, Trp promoted dissociation of nascent Trp‐tRNA Trp from bovine TrpRS (Merle et al , 1988). (Similarly, in the related class I IleRS, at least three independent experiments showed that, after aminoacylation, the binding of a new molecule of isoleucine promoted the dissociation of Ile‐tRNA Ile (Yarus and Berg, 1969; Eldred and Schimmel, 1972; Eldred and Schimmel, 1973). )…”
Section: Resultsmentioning
confidence: 99%
“…The calculated number of sites was 1.14; the dissociation constant was calculated to be 0.63 pmol L -1 (95% confidence intervals (C.I. ): 0,51-0.75 pmol L-l), which is of the same order of magnitude as the value of 0.19 pmol L -1 for interactions of beef TrpRS and tRNATrp [12,15].…”
Section: Estimation Of Dissociation Constant At 25 ~mentioning
confidence: 91%
“…We assume that tRNATrp transfers between TrpRS and TrpRS-tRNATrp complex quickly, and no stable complex exists. Merle also thought it likely that the association process of beef TrpRS and tRNATrp is comparatively fast [12]. Figure 4 shows schemes of the interactions.…”
Section: Interactions Between Trprs and Trna Trpmentioning
confidence: 98%